Cautho yojanāko prathama varsha (2027/028) ko pragati vivaraṇa (Śrī 5 ko Sarakāra, Rāshṭriya Yojanā Āyogako Sacivālaya, 1971)
Analytical report on the progress made during the first year (i.e. 1971) of the Fourth Five Year Plan in Nepal.